2020
DOI: 10.3389/fimmu.2020.01391
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From Adipose Tissue-Derived Stem Cells Affect Notch-miR148a-3p Axis to Regulate Polarization of Macrophages and Alleviate Sepsis in Mice

Abstract: Extracellular vesicles (EVs) from adipose tissue-derived stem cells have been reported to attenuate lipopolysaccharide (LPS) induced inflammation and sepsis while the specific mechanism is unclear. This study explored the underlying molecular mechanisms of EVs from adipose tissue-derived stem cells in reducing inflammation. LPS- induced macrophage models and mice model were established to mimic inflammation in vitro and in vivo . EVs were extracted from adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Similarly, miR-148a-3p was shown to be a mediator by which Notch promotes M1 polarization ( 80 ). Moreover, adipose stem cell-derived extracellular vesicles (EVs) could inhibit the Notch signaling pathway and M1 polarization to exert anti-inflammatory effects, which was associated with decreased expression of miR148a-3p ( 81 ).…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Similarly, miR-148a-3p was shown to be a mediator by which Notch promotes M1 polarization ( 80 ). Moreover, adipose stem cell-derived extracellular vesicles (EVs) could inhibit the Notch signaling pathway and M1 polarization to exert anti-inflammatory effects, which was associated with decreased expression of miR148a-3p ( 81 ).…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…It affects 20 million patients worldwide each year and accounts for a large portion of the mortality rate [ 141 ]. Several studies have found that MSC-derived EVs lowered systemic inflammation and alleviated organ damage in sepsis [ 142 , 143 , 144 ]. EVs from healthy AD-MSCs reduced the circulating level of TNF-α, and this led to a significant increase in the survival rate in a rat model of sepsis [ 142 ].…”
Section: Therapeutic Effects Of Evs On Inflammatory Diseasesmentioning
confidence: 99%
“…Another group examined the effect of AD-MSC-derived EVs on sepsis in mice. They administered AD-MSC-derived EVs and observed regulation of LPS-induced inflammation via the Notch-miR-148a-3p axis and consequent relief of sepsis [ 143 ]. In a recent study, super-repressor IκB (srIκB, a dominant active form of IκBα) was loaded into EVs, and the effect on sepsis-associated organ damage and mortality was observed [ 144 ].…”
Section: Therapeutic Effects Of Evs On Inflammatory Diseasesmentioning
confidence: 99%
“…In experimental models of sepsis obtained by LPS administration or by cecal ligation and puncture (CLP) MSC-derived EVs inhibited the development of disease by downregulating JMJD3 and inactivating the NF-κB signaling pathway through the selected transfer of miR-27b ( 122 ). EVs isolated from AD-MSCs have been shown to attenuate inflammation and protect from organ dysfunction by regulating the Notch-miR148a-3p signaling axis and decreasing macrophage polarization to M1 ( 123 ). In experimental s-AKI, the administration of EVs isolated from AD-MSCs exerted a renal protective effect through SIRT1 signaling pathway ( 124 ).…”
Section: Therapy With Sc-derived Evs In Different Forms Of Akimentioning
confidence: 99%